A species of the Asteraceae family (89-1-XIV) with anti-insect activity against the pest Sitophilus zeamais - Gonz?lez, Sayonara; Pino, Oriela; Herera, Rafael Segundo; Valenciaga, Nurys; Fortes, Dayleni; S?nchez, Yaima (Cuban Journal of Agricultural Science, 2010)
A completely randomized design was used to determine the principal groups of secondary metabolites, the anti-insect effect against Sitophilus zeamais, and the influence of the powders of the structural organs of the plant (89-1-XIV) on the germination of corn seeds. The treatments were the structural organs of the plant separately: leaf, stalk, and root, and a negative control, with four repetitions each. The antiinsect effect was assessed through the mortality, the emergence, the repellent effect on the adult insect, and the weight loss of the corn grain. For the powders of leaf, there were mortality values of 67.2 % in the adults of S. zeamais. The treatment with the highest mortality had the lowest emergence (38.7 %) and the lowest weight loss of the grain (10.75 %). The best repellent effect was obtained by using the leaf powders. In the percentage of germination, there were only significant differences in the leaves in respect to the rest of the treatments (P < 0.05). It is concluded that the plant showed diversity in the composition of secondary metabolites in each of the organs under study, and that the leaf powders at 1 % had anti-insect effect on S. zeamais. However, it is recommended to assess the use of leaves in the form of powder to protect the corn stored as seed because this could affect the germination. Key words: plant powders, secondary metabolites, Sitophilus zeamais.